Preparing Law Students for Information Governance. Issue 2 (2nd April 2016) - deMaine, Susan David
ABSTRACT: Information governance is a holistic business approach to managing and using information that recognizes information as an asset as well as a potential source of risk. Law librarians and legal information professionals are well situated to take leadership roles in information governance efforts, including instructing law students in information governance principles and practices. This article traces the development of information governance and its importance to the legal profession, offers a primer on information governance principles and implementation, and discusses how academic law librarians and other legal educators can teach information governance to law students using problem-based learning or similar pedagogical methods.